2007
DOI: 10.1158/1078-0432.ccr-06-2073
|View full text |Cite
|
Sign up to set email alerts
|

High Macrophage Infiltration along the Tumor Front Correlates with Improved Survival in Colon Cancer

Abstract: Purpose: The role of macrophages in tumorigenesis is complex because they can both prevent and promote tumor development. Experimental Design: Four hundred forty-six colorectal cancer specimens were stained with the pan-monocyte/macrophage marker CD68, and average infiltration along the tumor front was semiquantitatively evaluated using a four-grade scale. Each section was similarly scored for the presence of CD68 hotspots. Some aspects of macrophage-tumor cell interactions were also studied using in vitro coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
390
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(427 citation statements)
references
References 32 publications
29
390
2
6
Order By: Relevance
“…[12][13][14] Some studies relying on immunohistochemical staining of human colorectal cancers, in fact, indicate that macrophages along the tumor margin [31][32][33] and macrophages expressing VEGF 34 are associated with a good prognosis. Others have suggested that macrophages in colorectal cancer may have co-stimulatory functions in antitumor immunity 35 or may be able to induce tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Some studies relying on immunohistochemical staining of human colorectal cancers, in fact, indicate that macrophages along the tumor margin [31][32][33] and macrophages expressing VEGF 34 are associated with a good prognosis. Others have suggested that macrophages in colorectal cancer may have co-stimulatory functions in antitumor immunity 35 or may be able to induce tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on 26 and 30 patients, respectively, showed that low infiltration of macrophages correlated with more advanced colorectal cancer (45,46). A recent study indicated that a dense macrophage infiltration at the tumor front positively influenced prognosis in colon cancer (47). Hence, TAMs are an important feature of cancer and their level of infiltration into tumors has an important prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of cancer immune-surveillance has been supported by research showing that immune-deficiencies facilitate easy development of a neoplasm, further studies by animal models with inhibition of specific genes coding for the immune response resulted in a higher susceptibility to develop spontaneous or chemically-induced cancers (2,3). Previous studies showed that the infiltration of TAMs in colorectal cancer predicted a good prognosis (4)(5)(6)(7)(8). TAMs have been shown to be highly plastic cells that can display both tumor preventing (M1 macrophages) and tumor promoting functions (M2 macrophages) (9,10).…”
Section: Introductionmentioning
confidence: 99%